Production of endoglucanase and xylanase from indigenous strain of Aspergillus niger: optimization of cultural conditions - KAMIL, DEEBA; SINHA, ASHA (Indian Phytopathology, 2011)
A variety of microorganisms have been reported to produce cellulase and xylanase of which the most potent producers are the fungi. A number of indigenously isolated fungi were screened for cellulolytic and xylanolytic potential. In the present study, the enzyme production with purified carboxy methyl cellulose (CMC) and birch wood xylan was investigated and found to be promising. It was also observed that the production of endoglucanase reaches its maximum during exponential phase of growth, while xylanase during the stationary phase. Furthermore, the kinetics of endoglucanase and xylanse production from an indigenous strain of Aspergillus niger is reported when grown on different carbon containing natural substrates, for example, wheat straw, rice straw and corn straw. The endoglucanase and xylanse production were found maximum with wheat straw ie.142.34 U/g dry substrate and 2285.62 U/g dry substrate, respectively. Growth and enzyme production was affected by variations in temperature and pH. Highest production of endoglucanse and xylanase were noted at 25 Â°C and 30 Â°C with pH 6.0.